Egg drop dead - Chien, Vivien (Chien, Vivien. Noodle shop mystery., 2020)
"It was supposed to be a fancy, intimate dinner party by the pool. Instead, Lana Lee's first-ever catering event turns into full-course madness when a domestic worker is found dead. Is the party's host Donna Feng, the sweet-and-sour owner of the Asia Village shopping plaza where Ho-Lee is situated, somehow to blame? That's what Lana--whose plate is already plenty full with running the restaurant, pleasing her often-disapproving mother, and fretting over her occasionally-serious boyfriend Detective Adam Trudeau--must find out. Before the police arrived at the crime scene, Donna had entrusted an odd piece of evidence to Lana: a thumb drive shaped like a terra-cotta soldier. Now it's up to Lana to lead her own investigation, digitally and in real life, into a world of secrets involving Donna's earlier life in China, whether the victim had a dark agenda, and if the killer is still out there...and plans to strike again."--Page 4 of cover